EXPLORING THE EFFECTIVENESS OF GAME-BASED LEARNING (GBL) FOR ENHANCING STUDENTS’ CREATIVITY IN WRITING CLASS - Darma, Virga Putra; Solihah, Yuni Awalaturrohmah; Kartika, Viar Dwi (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2025)
This study investigates the efficacy of game-based learning (GBL) in the context of writing instruction, specifically examining its influence on students' creativity in Institut Prima Bangsa. The aim of this study is to ascertain whether GBL can foster enhanced creative writing abilities for the students. By analyzing the relative effectiveness of these pedagogical strategies, the study aspires to yield significant insights into the ways in which GBL affects students' writing competencies and creative expression. An experimental research design was utilized, comprising two distinct student groups: an experimental group engaged in writing instruction through GBL and a control group receiving traditional writing education. To evaluate the effectiveness of the instructional approaches, both groups underwent pre-tests and post-tests, which measured various dimensions of writing proficiency and creativity prior to and following the instructional phase. Subsequent statistical analyses were conducted to compare the outcomes of the two groups, with the objective of identifying any notable differences in results. The findings indicated that the experimental group, which participated in GBL, exhibited a marked enhancement in both writing skills and creativity relative to the control group that adhered to traditional instructional practices. This finding underscores the significant implications of the research for educational environments, particularly in the realms of language instruction and curriculum development. The findings highlight the novelty of this study in demonstrating how the integration of game-based learning strategies not only enhances student engagement but also introduces a creative pedagogical framework that stimulates students’ imaginative thinking in ways that traditional methods may not achieve.